2021
DOI: 10.1002/ijc.33504
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime alcohol intake, drinking patterns over time and risk of stomach cancer: A pooled analysis of data from two prospective cohort studies

Abstract: Alcohol consumption is causally linked to several cancers but the evidence for stomach cancer is inconclusive. In our study, the association between long‐term alcohol intake and risk of stomach cancer and its subtypes was evaluated. We performed a pooled analysis of data collected at baseline from 491 714 participants in the European Prospective Investigation into Cancer and Nutrition and the Melbourne Collaborative Cohort Study. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated for inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…26 We have previously shown associations for heavy alcohol intake over the lifetime with subtypes of stomach cancer using semiparametric group-based trajectory modeling. 27 Although most cohort studies have relied upon baseline alcohol intake (ie, intake closer to study enrolment) for their exposure variable, 10 we have demonstrated that baseline alcohol intake could be low for male former heavy drinkers. Our analyses using intake trajectories during the life course have also shown that using baseline intake alone is likely to miss risky drinking behaviors in early adult life especially in men (eg, TR5 early decreasing heavy and TR2 stable light trajectories had similar baseline alcohol intakes but contrasting intakes in early adulthood) for whom the model fit was also slightly better with the additional information provided by the trajectories.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…26 We have previously shown associations for heavy alcohol intake over the lifetime with subtypes of stomach cancer using semiparametric group-based trajectory modeling. 27 Although most cohort studies have relied upon baseline alcohol intake (ie, intake closer to study enrolment) for their exposure variable, 10 we have demonstrated that baseline alcohol intake could be low for male former heavy drinkers. Our analyses using intake trajectories during the life course have also shown that using baseline intake alone is likely to miss risky drinking behaviors in early adult life especially in men (eg, TR5 early decreasing heavy and TR2 stable light trajectories had similar baseline alcohol intakes but contrasting intakes in early adulthood) for whom the model fit was also slightly better with the additional information provided by the trajectories.…”
Section: Resultsmentioning
confidence: 80%
“…These findings were based on only 89 cancer deaths, risks for men and women were not assessed separately and the drinking patterns did not take into account the exact amount of alcohol consumed 26 . We have previously shown associations for heavy alcohol intake over the lifetime with subtypes of stomach cancer using semiparametric group‐based trajectory modeling 27 . Although most cohort studies have relied upon baseline alcohol intake (ie, intake closer to study enrolment) for their exposure variable, 10 we have demonstrated that baseline alcohol intake could be low for male former heavy drinkers.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of alcohol drinking, previous studies revealed that chronic alcohol drinking could combine HP infection with IL-10 (interleukin-10) inhibition to induce gastric tumorigenesis [38] . Additionally, alcohol consumption could lead to direct cellular injury and gene mutation by enhancing the penetration of carcinogens into cells [39] .…”
Section: Discussionmentioning
confidence: 99%
“…The top 3 to 6 common cancers are gastric, liver, colorectal, and esophageal cancers in Anhui Province, which are infection-related and poverty-related cancers. These cancers are associated with unhealthy lifestyles, such as alcohol consumption, 17 pickled foods, 18 eating hot food, 19 and chronic infectious agents. 20 In order to address this public health concern, the Huaihe Valley Cancer Early Diagnosis and Treatment Program has been providing screening services for upper gastrointestinal and liver cancers in Anhui Province since 2007.…”
Section: Discussionmentioning
confidence: 99%